Safety evaluation of food enzyme glucan 1,4‐α‐maltohydrolase produced with a genetically modified Bacillus subtilis (strain MAM) - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF); Vittorio Silano; Claudia Bolognesi; Laurence Castle; Kevin Chipman; Jean‐Pierre Cravedi; Paul Fowler; Roland Franz; Konrad Grob; Rainer Gürtler; Trine Husøy; Sirpa Kärenlampi; et al. (EFSA Journal, 2018)
Abstract The food enzyme considered in this opinion is a glucan 1,4‐α‐maltohydrolase (maltogenic α‐amylase; EC 3.2.1.133) produced with the genetically modified Bacillus subtilis strain MAM by the company DSM Food Specialties B. V. The food enzyme contains neither the production microorganism nor recombinant DNA; therefore, no environmental risk assessment is required. However, the Panel emphasises that this conclusion only covers the food enzyme recovered via filter press. The glucan 1,4‐α‐maltohydrolase is intended for use in baking processes. Based on the maximum use levels recommended and individual consumption data from the EFSA Comprehensive European Food Consumption Database, dietary exposure to the food enzyme‐total organic solids (TOS) was estimated to be up to 0.175 mg TOS/kg body weight (bw) per day in European populations. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rodents. A no observed adverse effect level (NOAEL) was derived (986 mg TOS/kg bw per day for both males and females), which, compared with the dietary exposure, results in a sufficiently high margin of exposure. The allergenicity was evaluated by comparing the amino acid sequence to those of known allergens; one match was found. However, the Panel considered that there are no indications for food allergic reactions to this glucan 1,4‐α‐maltohydrolase by dietary exposure. No safety concerns were identified in relation to the genetic modifications, the manufacturing process, the compositional data provided, as well as the exposure, allergenicity and systemic toxicity assessments. However, owing to the incompleteness of the genotoxicity data, the Panel is not able to conclude on the safety of the food enzyme.